Leaf beetles of the subfamily eumolpinae (coleoptera; chrysomelidae) from Bali, Indonesia.) - Lev N. Medvedev; Haruo Takizawa (Pusat Sistematik Serangga ,UKM, 2011)
A total of 31 species of the subfamily eumopinae (Coleoptera chrysomelidae are listed from Bali, Indonesia. Eight new species and 2 new subspecies for callisina are described:Colaspoides purpurata,platycorynus hijau, rhyparida microdentata,tricliona oculata,xanthonia insularis n.ssp from Bali.Two new subspecies for callisina fasciata n.ssp from Bali and Java respectivrly.